Bryozoans from RV Sonne deep-sea cruises SO 167 ‘Louisville’ and SO 205 ‘Mangan’ - Matsuyama, Kei; Janssen, Annika; Arbizu, Pedro Martínez; Martha, Silviu O.; Freiwald, André (Zootaxa, 2014)
The German research vessel Sonne is operating in the Pacific, Southern and Indian Oceans. In the current stage of development in Pacific deep-sea mining projects, prior understanding of biodiversity patterns in the affected regions is one of the major research goals of the RV Sonne cruises. In the present study, nine bryozoan species are reported from the Equatorial East Pacific and the Kermadec–Tonga Ridge, collected during RV Sonne cruises SO 167 “Louisville” and SO 205 “Mangan”, from 356–4007 m. Two new species, Raxifabia oligopora n. sp. and Opaeophora triangula n. sp., are described.